Treatment-resistant depression and major depression with suicide risk-The cost of illness and burden of disease - Sousa, Rute Dinis (2022)
Funding The present work received support from Janssen-Cilag Farmacêutica, Lda, as an Unrestricted Grant. Janssen-Cilag had no role in the execution of the study, including analyses and interpretation of results.